Les bois et les objets composites (bois-métal) de la fouille du parking Anatole France à Tours (Indre-et-Loire) - Pierre Mille; Agnès Couderc; Nicolas Fouillet; Bertrand Moine; Françoise Yvernault (Revue Archéologique du Centre de la France)
Wood and wood-metal composite objects unearthed in the ditch of the city wall of Tours date from the very end of the fifteenth century and the first quarter of the sixteenth century. They are an important milestone for the knowledge of everyday life and that of technical expertise to this pivotal period.The xylologic body from the excavation of the Anatole France carpark is one of the most informative French ensembles, not only for the number of objects and fragments studied: 430, but also the quality of preservation of some artifacts. They come from a ditch that drains calibrated intakes originating from domestic areas on both sides of the street Ragueneau.It may be noted that the impressive series of instruments and cooking utensils for the conservation and consumption of food including a collection of table trenchers is completely unparalled.Among the domestic effects and pharmacopoeia, the imposing series of combs will enable a precise date for the context of this discovery. Apart from two backgammon tokens and an exceptional bishop from a game of chess classified under games, a substantial number of tools have been identified. They relate to a variety of activities such as textiles, those of shoemaking, boating, and carpentry. The horse grooming tools, the most original part of this corpus, are totally new.This set can also address through the anatomical identification and dendro-provenance the river transport of some exogenous wood work probably from the Massif Central, and the commercialization of several types of objects produced outside the region on a proto-industrial scale, such as cork stoppers or boxwood combs. Placed in its historical context, ie in 1482-1483 between the open gate of the Ragueneau and the first filling-up of the city walls in the middle of the sixteenth century, the landscape that is emerging around is that of an area which was well done-up and maintained, in a word “urbanized”.